4y
M=3 because y+y+y= 3xY and MY= MxY
(x + y)(x + y)(x + y)
2 + (5 + y) = 7 + y
3x+7x+3+y= 10x+3+y
4y
-2(y plus 5) plus y?
M=3 because y+y+y= 3xY and MY= MxY
Well, honey, y plus y plus y is just 3y. It's as simple as that. No need to overcomplicate things, darling.
(x + y)(x + y)(x + y)
2 + (5 + y) = 7 + y
-6
3x+7x+3+y= 10x+3+y
To simplify Y plus Y, you can combine the like terms. In this case, both Y terms are like terms because they have the same variable. When you add them together, you get 2Y. Therefore, Y plus Y simplifies to 2Y.
It is 5x+y
y += x means the value y+x is first calculated, and the resulting value is then assigned to y. It is equivalent to y = y+x
The answer to Y x plus 5 Y 6 is Y(x+5Y5).One possible solution to y x plus 5 y 6 is Y(x+5Y5).